Beyond Diversification : what every investor needs to know about asset allocation - Page, Sebastien (McGraw Hill-Ascent Audio, 2021)
Asset allocation is the key to investing performance. Unfortunately, no single approach works perfectly-developing the right balance requires a clear-eyed look at the many models available to you, various investing methodologies, and your or your client's level of risk tolerance. And that's where this important guide comes in. Written by a leading allocation expert from T. Rowe Price, Beyond Diversification provides the knowledge, insights, and approaches you need to make the best allocation decisions for your goals. This deep dive into the how's and why's of asset allocation is organized by the three decisive components of a successfully allocated portfolio: - Return Forecasting discusses the desired return investors seek. - Risk Forecasting covers the level of risk investors are prepared to assume to achieve that return. - Portfolio Construction calibrates the stock-bond mix that balances the risks and returns. With examples from T. Rowe Price's asset allocation team showing you how the process works in the real world, Beyond Diversification provides everything you need to find the asset combination that will deliver the results you seek.